Surgical Outcome of Limberg’s Flap Reconstruction in the Treatment of Pilonidal Sinus Disease in a Community Hospital - Karki, B.; Rajbhandari, N. (Kathmandu University Medical Journal, 2022)
Background Pilonidal sinus disease is an acquired condition that commonly arises in the hair follicles of the gluteal cleft with male predominance. Different treatment modalities have been described in the literature ranging from simple incision and drainage, wide local excision to complex plastic flaps. Objective To evaluate the efficacy and outcome of Limberg’s flap reconstruction in a community hospital. Method This is a prospective study conducted over two-year duration in forty-two patients in the department of Surgery at Dhulikhel Hospital Kathmandu University Hospital from January 2017 till December 2018. Result Total of 42 patients were operated ranging from 16-31 years with mean of 22.86 years, male to female ratio was 7.5:1, 52% were students and 19% were drivers. Mean operative duration was 61.86±25.3 minutes, length of hospital stay was 2.83±1.68 days, mean duration of drain in situ was 4±1.34 days, mean days for return to work was 14.5±5.7. We had a complication rate of 9.52% out of which 4.76% had seroma, 2.38% hematoma, 2.38% wound infection, and there was no flap necrosis or recurrence. Conclusion It is a simple, easy to learn and safe procedure with good cosmetic results and low recurrence rate. It can be considered as an alternative to other flap and plasty procedures